Sorry Im not quite getting it .....
could you elaborate please...
from what i read....
c^2 + d^2 can be expressed as (2^k)*p1..pk*q1...ql
a^2 + b^2 can be expressed as (2^g)*s1..sm*t1...tn
where p1...pk and s1...sm are primes =1 mod 4
and where q1...ql and t1...tn are primes =3 mod 4 with even power...
then
a^2 + b^2 = 6( c^2 + d^2 )
can be expressed as
(2^g)*s1..sm*t1...tn = 6*(2^k)*p1..pk*q1...ql
am i on the right track... I don't really know where to go from there
Another guy posted this solution is this correct
MathBin.net - Untitled